2008
DOI: 10.1071/ch07130
|View full text |Cite
|
Sign up to set email alerts
|

SEM and BET Methods for Investigating the Structure and Morphology of Co - Ce Catalysts for Production of Light Olefins

Abstract: Co–Ce catalysts prepared by the coprecipitation method were tested for production of light olefins. The effect of different preparation conditions including the [Co]/[Ce] molar ratio, aging time, calcination conditions, different supports, and loading of optimum support on the structure and catalytic performance of different catalysts were investigated. It was found that catalyst containing 80% Co/20% Ce/15% SiO2, which was aged for 2 h and calcined at 600°C for 6 h, is the optimum modified catalyst for the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 36 publications
0
14
0
Order By: Relevance
“…In our previous study, we demonstrated the importance of ageing time with respect to catalyst activity for oxidation of CO by mixed copper manganese oxide and mixed copper zinc oxide catalyst (Hutchings et al, 1996(Hutchings et al, , 1998Taylor et al, 1999Taylor et al, , 2003Whittle et al, 2002;Mirzaei et al, 2003aMirzaei et al, ,b,c, 2005a and for hydrogenation of CO by mixed of cobalt-iron oxide, cobalt manganese oxide and cobalt cerium oxide catalysts for FischereTropsch synthesis (Mirzaei et al, 2005a(Mirzaei et al, ,b, 2006a(Mirzaei et al, ,b, 2007(Mirzaei et al, , 2008. The results of all of these investigations have shown that the ageing of the precipitates obtained by co-precipitation leads to phase changes toward forms that are thermodynamically stable.…”
Section: Effect Of Ageing Timementioning
confidence: 90%
See 3 more Smart Citations
“…In our previous study, we demonstrated the importance of ageing time with respect to catalyst activity for oxidation of CO by mixed copper manganese oxide and mixed copper zinc oxide catalyst (Hutchings et al, 1996(Hutchings et al, , 1998Taylor et al, 1999Taylor et al, , 2003Whittle et al, 2002;Mirzaei et al, 2003aMirzaei et al, ,b,c, 2005a and for hydrogenation of CO by mixed of cobalt-iron oxide, cobalt manganese oxide and cobalt cerium oxide catalysts for FischereTropsch synthesis (Mirzaei et al, 2005a(Mirzaei et al, ,b, 2006a(Mirzaei et al, ,b, 2007(Mirzaei et al, , 2008. The results of all of these investigations have shown that the ageing of the precipitates obtained by co-precipitation leads to phase changes toward forms that are thermodynamically stable.…”
Section: Effect Of Ageing Timementioning
confidence: 90%
“…In our previous works (Mirzaei et al, , 2008 we demonstrated the importance of calcination conditions with respect to the catalyst activity for the hydrogenation of CO by mixed cobalt cerium oxides. The results of these investigations have shown that the calcination conditions of the precipitates obtained by co-precipitation lead to the phase changes toward forms that are more thermodynamically stable.…”
Section: Effect Of Calcination Parametersmentioning
confidence: 99%
See 2 more Smart Citations
“…In our previous study, we demonstrated the importance of aging time with respect to catalyst activity for oxidation of CO by mixed copper manganese oxide and mixed copper zinc oxide catalysts [27][28][29][30][31][32][33][34][35] and for hydrogenation of CO by mixed of cobalt-iron oxide, cobalt-manganese oxide, and cobaltcerium oxide catalysts for Fischer-Tropsch synthesis [36][37][38][39][40]. In all of these investigations, our results have shown that the aging of the precipitates obtained by coprecipitation leads to phase changes toward the forms, which are more stable thermodynamically.…”
Section: Effect Of Aging Timementioning
confidence: 99%